Analysis of the Effect of Poverty, Illiteracy, Unemployment, Years of Schooling, and Life Expectancy on Indonesia's Economic Growth - I Made Gde Yudi Darmawan; Mansur Afifi; Irwan Suriadi (Tinta Emas Institute, 2023)
Economic growth is a process of continuous change in a country's economy towards a better situation over a certain period. An economy is said to experience a change if the level of economic activity is higher than that achieved in the previous year. This study aims to determine the effect of independent variables (Poverty, Illiteracy, Unemployment, Years of Schooling, and Life Expectancy) partially or simultaneously on the dependent variable (Economic Growth) in Indonesia in 2010-2021. This research uses time series data on poverty, illiteracy, unemployment, school length, and life expectancy for 11 years. In addition, this study uses multiple linear regression analysis methods as the analytical tool used. The results of this study indicate that the variables of poverty, illiteracy, and unemployment have a negative effect on economic growth in Indonesia. While the variables of years of schooling and life expectancy have a positive effect on economic growth in Indonesia. The variables of poverty, illiteracy, unemployment, years of schooling, and life expectancy simultaneously affect economic growth.